PENGAKUAN ANAK ANGKAT SEBAGAI AHLI WARIS MENURUT HUKUM PERDATA DI INDONESIA - Rahmi, Ita (Universitas 17 Agustus 1945 Samarinda, 2025)
ABSTRACT. Child adoption is a form of protection and fulfillment of the rights of children in families who cannot have biological children. In the context of civil law in Indonesia, adoption of children has various legal implications, especially in terms of the position of adopted children as heirs. This paper aims to examine how the legal recognition of adopted children as heirs according to the provisions of the applicable civil law in Indonesia. This study uses a normative juridical method with a legislative approach and literature study. The results of the study show that adopted children have a legal status after a court determination and can be equated with biological children in terms of inheritance rights, both based on the Civil Code and related laws such as the Child Protection Law and Government Regulation Number 54 of 2007. However, its implementation still faces obstacles, especially related to social recognition and inheritance practices that are not always in accordance with legal provisions. Therefore, consistent socialization and law enforcement are needed so that the rights of adopted children as heirs can be guaranteed fairly.Keywords: Adopted Children, Inheritance Rights, Civil Law, Adoption Of Children, Heirs.